Infrared vibrational spectra, electronic structures, and formation reactions of polypyrrolic mono‐ and bis‐actinyl complexes: A relativistic DFT study. Issue 13 (3rd April 2017) - Zheng, Xiu‐Jun; Qu, Ning; Xuan, Li‐Chun; Pan, Qing‐Jiang
Abstract: The development of synthetic techniques has enabled synthesis and characterization of a series of mono and bis ‐uranyl complexes of octadentate polypyrrolic macrocycles such as aryl‐lined H4 L Ar and anthracenyl‐linked H4 L, which is complemented by theoretical investigation via extending to more toxic and radioactive transuranics. The relativistic density functional theory (DFT) study has been dedicated to twelve actinyl complexes supported by the H4 L ligand. The actinides include U, Np, and Pu elements, and either one or two is rendered in complexes with oxidation states of V or VI. Calculated symmetric/asymmetric An = O stretching vibrational frequencies show the decreasing trend along U, Np, and Pu, which is consistent with calculated bond orders. The hydrogen bonds between –yl endo ‐oxo and remaining hydrogen atoms of pyrrolides in mononuclear complexes cause pronounced redshift of An = O vibrational frequencies compared to those in binuclear complexes, so does the reduction from hexa ‐ to penta valent complexes. The electronic structures of actinyl complexes were calculated. For example, B‐pyU VI possesses low‐lying U(5 f )‐character virtual orbitals, where f (δ) and f (ϕ) orbitals occur in low‐energy region and π‐type ones are residing further high; the σ*(U = O) and σ(U = O) orbitals are significantly split over 7 eV. The previous experimental observation that the 1:1 reactions between uranyl salts and the macrocycle tend to give a mixture of bis ‐ and mono ‐uranyl complexes, with bis‐ the major product, has been corroborated by computational studies of the thermodynamics of the reactions. Abstract : The synthesis and characterization of mono and bis ‐uranyl(VI) complexes of a polypyrrolic macrocycle have been complemented by the relativistic density functional theory studies that show the potential of these compounds for chelating even more toxic and radioactive transuranic ions and the more difficult to access V oxidation state. A step‐wise reaction pathway for the reaction has been proposed, consistent with the yield of bis ‐uranyl(VI) complex as experimentally isolated major product.